INTERDISCIPLINARY CONNECTIOS OF COMPUTER SCIENCE AND MATHEMATICS IN THE STUDY OF PROBABILITY THEORY AND MATHEMATICAL STATISTICS - Saifetdinova С.; Tleulesova А.; Seisen У. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The proposed article outlines the possibilities, purpose, and relevance of interdisciplinary communication of computer science and mathematics subjects, which can be used in the study of the section “probability theory and mathematical statistics" in mathematics lessons at school. Preparing a person who meets the requirements of modern society is one of the urgent tasks of the education system. And in order to meet the criteria, it is necessary to improve the quality of education by combining modern technologies and methods in the education system. The article discusses the ways and effectiveness of solving problems encountered in the school mathematics course on Probability Theory and mathematical statistics using information technology, including the Python programming language, which will be held in computer science lessons. The establishment of interdisciplinary connections in the process of teaching mathematics is an indispensable opportunity to increase the motivation of a student to study mathematics, develop computational skills, and improve functional literacy. The purpose of the work is to show ways to solve the problem using the Python programming language when studying the section “probability theory and mathematical statistics” in secondary schools. The article examines the works published so far on the problem under study and considers a way to deduce some of the problems encountered in the school curriculum using the Python program.